Oncogenic and tumor suppressive roles of polo-like kinases in human hepatocellular carcinoma - Pellegrino, Rossella; Calvisi, Diego F.; Ladu, Sara; Ehemann, Volker; Staniscia, Tommaso; Evert, Matthias; Dombrowski, Frank; Schirmacher, Peter; Longerich, Thomas (Hepatology, 2010)
Polo-like kinase (PLK) proteins play critical roles in the control of cell cycle progression, either favoring or inhibiting cell proliferation, and in DNA damage response. Although either overexpression or down-regulation of PLK proteins occurs frequently in various cancer types, no comprehensive analysis on their function in human hepatocellular carcinoma (HCC) has been performed to date. In the present study, we define roles for PLK1, PLK2, PLK3, and PLK4 during hepatocarcinogenesis. Levels of PLK1, as assessed by means of real-time reverse-transcription PCR and western blot analysis, were progressively increased from nonneoplastic surrounding liver tissues to HCC, reaching the highest expression in tumors with poorer outcome (as defined by the length of patients' survival) compared with normal livers. In sharp contrast, PLK2, PLK3, and PLK4 messenger RNA and protein expression gradually declined from nontumorous liver to HCC, with the lowest levels being detected in HCC with shorter survival. In liver tumors, PLK2-4 down-regulation was paralleled by promoter hypermethylation and/or loss of heterozygosity at the PLK2-4 loci. Subsequent functional studies revealed that PLK1 inhibition led to suppression of cell growth in vitro, whereas opposite effects followed PLK2-4 silencing in HCC cell lines. In particular, suppression of PLK1 resulted in a block in the G2/M phase of the cell cycle and in massive apoptosis of HCC cells in vitro regardless of p53 status. Conclusion: PLK1-4 proteins are aberrantly regulated and possess different roles in human HCC, with PLK1 acting as an oncogene and PLK2-4 being presumably tumor suppressor genes. Thus, therapeutic approaches aimed at inactivating PLK1 and/or reactivating PLK2-4 might be highly useful in the treatment of human liver cancer. (HEPATOLOGY 2010.)
Erstmals veröffentlicht: 30 November 2009
Gesehen am 30.06.2023